Respuestas
Respuesta dada por:
3
a)
![6 \times (8 - 12) - 3 \times (5 - 11) = \\ 6 \times ( - 4) - 3 \times ( - 6) = \\ - 24 + 18 = \\ - 6 6 \times (8 - 12) - 3 \times (5 - 11) = \\ 6 \times ( - 4) - 3 \times ( - 6) = \\ - 24 + 18 = \\ - 6](https://tex.z-dn.net/?f=6+%5Ctimes+%288+-+12%29+-+3+%5Ctimes+%285+-+11%29+%3D++%5C%5C+6+%5Ctimes+%28+-+4%29+-+3+%5Ctimes+%28+-+6%29+%3D++%5C%5C++-+24++%2B+18+%3D++%5C%5C++-+6)
b)
![4 \times (13 - 8) + 3 \times (9 - 15) = \\ 4 \times (5) + 3 \times ( - 6) = \\ 20 - 18 = \\ 2 4 \times (13 - 8) + 3 \times (9 - 15) = \\ 4 \times (5) + 3 \times ( - 6) = \\ 20 - 18 = \\ 2](https://tex.z-dn.net/?f=4+%5Ctimes+%2813+-+8%29+%2B+3+%5Ctimes+%289+-+15%29+%3D++%5C%5C+4+%5Ctimes+%285%29+%2B+3+%5Ctimes+%28+-+6%29+%3D++%5C%5C+20+-+18+%3D++%5C%5C+2)
b)
Preguntas similares
hace 6 años
hace 6 años
hace 9 años
hace 9 años